Duane retraction syndrome in a Nigerian child - Olawoye, Olusola Oluyinka (Pan Afr Med J, 2014)
We report a case of a four year old Nigerian girl who presented to the paediatric unit of our eye clinic with complaints of a squint on looking to the right side and reduction in the size of the right eye when looking to the left. On examination, she had right exotropia in the primary position of gaze. There was limitation of abduction and widening of the palpebral fissure of the right eye on right gaze. On left gaze there was narrowing of the palpebral fissure of the right eye with marked limitation of adduction and an upshoot, or occasionally a downshoot, of the eyeball. This report demonstrates that Duane's syndrome occurs in West Africa. Therefore, detailed examination of all patients with squints is important to ensure accurate diagnosis and appropriate management of the patient's condition.